Ripoptocide – A Spark for Inflammation - Ang, Rosalind L.; Chan, Mark; Ting, Adrian T. (Frontiers in Cell and Developmental Biology, 2019)
The clinical success of biologics that inhibit TNF (Tumor Necrosis Factor) in inflammatory bowel diseases (IBD), psoriasis and rheumatoid arthritis (RA) has clearly established a pathogenic role for this cytokine in these inflammatory disorders. TNF binding to its receptors activates NFB and MAPK signaling, inducing the expression of downstream pro-inflammatory genes. This is thought to be the primary mechanism by which TNF elicits inflammation. TNF is also a well-known trigger of caspase-dependent apoptosis or caspase-independent necroptosis. Whether cell death has any role in TNF-mediated inflammation has been less clear. Emerging data from animal models now suggest that cellular demise caused by TNF may indeed provoke inflammation. The default response of most cells to TNF stimulation is survival, rather than death, due to the presence of two sequential cell death checkpoints. The early checkpoint is transcription-independent involving the non-degradative ubiquitination of RIPK1 to prevent RIPK1 from becoming a death-signaling molecule. The later checkpoint requires the induction of pro-survival genes by NFB-mediated transcription. When the early checkpoint is disrupted, RIPK1 initiates cell death and we suggest the term ripoptocide to describe this manner of death (encompassing both apoptosis and necroptosis). The sensitivity of a cell to ripoptocide is determined by the balance between regulatory molecules that enforce and those that disassemble the early checkpoint. As there is evidence suggesting that ripoptocide is inflammatory, individuals may develop inflammation due to ripoptocide brought about by genetic, epigenetic or post-translational alteration of these checkpoint regulators. For these individuals, drugs that reinforce the early checkpoint and inhibit ripoptocide could be useful in ameliorating inflammation.